The Dynamic Effects of Neutral and Investment‐Specific Technology Shocks - Fisher, Jonas D. M. (Journal of Political Economy, 2006)
The neoclassical growth model is used to identify the short‐run effects of neutral technology shocks, which affect the production of all goods homogeneously, and investment‐specific shocks, which affect only investment goods. The real equipment price, crucial for identifying the investment shocks, experiences an abrupt increase in its average rate of decline in 1982, so the analysis is based on a split sample. On the basis of the preferred specification, the two technology shocks account for 73 percent of hours’ and 44 percent of output’s business cycle variation before 1982, and 38 percent and 80 percent afterward. The shocks also account for more than 40 percent of hours’ and 58 percent of output’s forecast errors over a three‐ to eight‐year horizon in both samples. The majority of these effects are driven by the investment shocks.